Strategi Nafkah Petani Perkotaan Pulau Kecil (Studi Kasus Kecamatan Leitimur Selatan Kota Ambon) - August Ernst Pattiselanno; Edizon Jambormias; Junianita Fridianova Sopamena (Jurnal Sosial Humaniora, 2018)
Farmers who live along the coastal of a small island have various ways tofulfill their needs. The ways to fulfill their needs depend on various habits thathave been carried out since a long time ago. The objective of this research is toanalyze livelihood strategies designed by the societies in the small island.Research was located in South Leitumur District, Ambon City. The site ofresearch was of two sub-districts, namely Hutumuri and Leahari. Sample offarmers were determined purposively from both sub-districts, resulting in 69farmers, precisely 51 farmers in Hutumuri and 18 farmers in Leahari. Datawere collected from depth interview and analyzed with simple tabulationaccompanied with descriptive explanation. Result of the research indicatedthat there are three livelihood strategies designed by coastal communities inSouth Leitimur District, namely first, developing natural/farming resourcepotentials by increasing the quantity of commodities that have potentialcapability to satisfy daily necessities; second, developing natural/farmingresource potentials in wider sense, which concerns with developing potentialsof coastal area as fishing spot; and third developing human resource potentialsby providing job opportunity out of farming and improving the existing skillsowned by farmer household.